The Lupus Ratio Test – An Interlaboratory Study on the Detection of Lupus Anticoagulants by an APTT-based, Integrated, and Semi-quantitative Test - Jacobsen, E. M.; Barna-Cler, L.; Taylor, J. M.; Triplett, D. A.; Wisløff, F. (Thrombosis and Haemostasis, 2000)
The Lupus Ratio (LR) test for lupus anticoagulants integrates screening, mixing with normal plasma and confirmation procedures into one assay. The sensitivity and reproducibility of the APTT based version of this assay was tested in an interlaboratory study that was part of the Fifth International Survey of Lupus Anticogulants (ISLA-5).One LA negative plasma containing heparin, six LA positive plasmas and a normal pooled plasma (NP) were distributed to 31 laboratories world-wide together with two APTT reagents, one with a high and one with a low phospholipid concentration. The laboratories performed two APTTs, one with each reagent, on 1 : 1 mixtures of test plasma and NP. The ratio between the two clotting times was divided by the corresponding ratio for the NP. This final ratio is the LR of that plasma. The overall sensitivity was found to be 95.1%, and the normal, heparin-containing sample was reported to be negative by all the laboratories.When the results were grouped in low, medium and high positive plasmas, a “consensus” regarding the strength of each plasma was easily found. 85.0% of the results were in agreement with this consensus.This study shows that with the LR test, it is possible to obtain high interlaboratory agreement regarding the presence or absence of LA as well as the semi-quantification of this inhibitor.Appendix, please see p. 708.
Keywords: Lupus anticoagulants; activated partial thromboplastin time (APTT); reproducibility of results